Sabo Bobaljević and the translation of his Italian verses - Malinar, Smiljka (2010)
The Dubrovnik poet Savino de’ Bobali Sordo (Sabo Babaljević Glušac) left in all 16 compositions written in Croatian and 216 poems in Italian. This disproportion should perhaps be ascribed to the manuscript form of transmission of Bobaljević’s Croatian verses (which could be the vestiges of a much larger oeuvre that has been lost in the meantime), whereas the Italian verses have been preserved in printed form. Their posthumous publication in Venice in 1584 under the title Rime amorose e pastorali e satire was facilitated by the poet’s brothers and rich relative Marin Bobaljević. There is no doubt that Bobaljević, member of the local Accademia dei Concordi, was primarily occupied with writing verses in Italian that were, in most of his works, fully at one with the stylistic standards of Bembo’s Petrarchism, then the dominant trend in the sphere of elevated poetry. The Croatian verses are heterogeneous in form and in terms of themes, and give the impression of being the outcome of experimentation. In them the Petrarchism remodelled by Bembo has left almost no trace whatsoever ; the only composition that might be referred to the influence of the Bembo aesthetic is contaminated by stylisation into the vernacular idiom. Most of the other, with their formalist mannerism of Provencal and late Latin derivation take us back to the archaic, strambotto version of Petrarchism, the status of which in Bobaljević’s time and in Dubrovnik was questionable (a conclusion that the poet himself suggests in some of his verses). Hence they are closer, for example, to the Ranjina than to the Bobaljević Italian collection, and its fluent, musical verses, which with untroubled ease interweave the motifs and formal assemblages characteristic of the then Petrarchan mainstream ; the occasional innovations are an echo of the testing of the canonical Petrarchist forms by the generation of poets contemporary with him. An exception is the segment of satires and epistles, derived from the same archetypal pattern. The paper adduces in broad lines the features of the translations of Bobaljević’s verses into Croatian by Frano Čale, published in the edition Pjesme talijanke/Italian Poems. Čale has with a very careful selection composed a corpus of Bobaljević’s best poems that – if they are the most acceptable for the present-day reader – give a somewhat untruthful picture of his poetic attainments, for his Italian oeuvre as a whole shows him to be much more mediocre and conventional than he appears in the idealised image given by Čale and other authors who have concerned themselves with his verses – Milica Popović, Đuro Körbler and Arrigo Zink (the last two raised the question of Bobaljević’s place within Italian and/or Croatian literature).
Projekt MZOS
ENG